Dominance Testing of Social Sector Expenditures and Taxes in Africa - Sahn, David (IMF Working Papers; Working Paper ;, 1999)
This paper examines the progressivity of social sector expenditures and taxes in eight sub-Saharan African countries. It uses dominance tests to determine whether health and education expenditures redistribute resources to the poor. The paper finds that social services are poorly targeted. Among the services examined, primary education tends to be most progressive, and university education is least progressive. The paper finds that many taxes are progressive as well as efficient, including some broad-based taxes such as the VAT and wage taxation. Taxes on kerosene and exports appear to be the only examples of regressive taxes.